Performance Analysis of Three Transition Mechanisms between IPv6 Network and IPv4 Network: Dual Stack, Tunneling and Translation - Hossain, Md. Asif; Podder, Durjoy; Jahan, Sarwar; Hussain, Mustafa (International Journal of Computer (IJC), 2016)
Due to the increasing demand of the Internet, we are facing a great problem of the depletion of our existing IPv4 (Internet Protocol version 4) network. To solve the situation, we have to use IP version 6 in coming years. But the IPv4 network will not be opt out, but also coexist with IPv6 network. For the transition from IPv4 to IPv6 and vice versa, there are three prominent transition mechanisms are used. They are Dual Stack, Tunneling and Translation. In this paper, the performances of these three mechanisms have been analyzed. IPv6 header format, its security and the routing also have been focused. For the simulation Packet Tracer simulation software has been used.